The importance of business incubation in developing countries: case study approach. (2015) - Al-Mubaraki, Hanadi Mubarak; Busler, Michael
Today business incubation is considered a powerful tool in developed and developing countries alike. Business incubators (BI) are among an assortment of initiatives to stimulate and support economic growth by promoting the creation and development of innovative companies. The aim of this paper is to identify the strengths and weaknesses of business incubation in developing countries. This paper uses a qualitative methodology based on three case studies of incubator programs in the countries of Bahrain, Saudi Arabia, and the United Arab Emirates. In addition to the case studies, a wide literature review and the authors' professional experience on the topic provide the foundation for this paper. The findings of this research present guidelines for practitioners including policy makers, governments, institutions, and funded organisations. The findings also contribute useful information to the current literature for academicians interested in the incubator model.